2013
DOI: 10.1186/1477-3155-11-14
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic capture from blood rescues molecular motor function in diagnostic nanodevices

Abstract: BackgroundIntroduction of effective point-of-care devices for use in medical diagnostics is part of strategies to combat accelerating health-care costs. Molecular motor driven nanodevices have unique potentials in this regard due to unprecedented level of miniaturization and independence of external pumps. However motor function has been found to be inhibited by body fluids.ResultsWe report here that a unique procedure, combining separation steps that rely on antibody-antigen interactions, magnetic forces appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…While Bachand and Bachand found that several common environmental contaminants are well tolerated by kinesins and microtubules, Korten et al demonstrated that specifically blood, plasma, and serum even at hundred-fold dilution interfere with the operation of kinesin- and myosin-driven systems . Kumar et al solved this problem by capturing analytes from serum, exchanging the buffer, and then introducing the motors . Clearly, protein engineering to mitigate adverse effects, protected environments or effective packaging solutions are needed.…”
Section: Limitations and Challengesmentioning
confidence: 99%
“…While Bachand and Bachand found that several common environmental contaminants are well tolerated by kinesins and microtubules, Korten et al demonstrated that specifically blood, plasma, and serum even at hundred-fold dilution interfere with the operation of kinesin- and myosin-driven systems . Kumar et al solved this problem by capturing analytes from serum, exchanging the buffer, and then introducing the motors . Clearly, protein engineering to mitigate adverse effects, protected environments or effective packaging solutions are needed.…”
Section: Limitations and Challengesmentioning
confidence: 99%
“…8,18 This may be further improved using enhanced fluorescence detection approaches 20,[60][61][62] and elimination of background fluorescence as well as magnetic pre-separation steps. 63…”
Section: Towards Practical Diagnostics Applicationsmentioning
confidence: 99%
“…Protein adsorption to surfaces is a ubiquitous and extremely important phenomenon. Whereas it may be unwanted in several instances, it has also been widely exploited in biotechnology as well as in fundamental biophysical and biochemical investigations . For instance, antibodies, or other protein-based recognition molecules, are adsorbed to detector surfaces in biosensing and proteomics , applications. In addition, fundamental functional studies often rely on surface adsorption of receptors and protein nanomachines. One widely used assay of the latter type is the in vitro gliding motility assay.…”
mentioning
confidence: 99%
“…Modified versions of the assay may also be applied to noncytoskeletal motors, such as processive DNA enzymes . In vitro gliding motility assays have also enabled a variety of nanotechnological applications, for example, in nanoseparation and biosensing , and more recently, parallel biocomputation . Many of these applications require nano/microstructured surfaces for physically and chemically confined filament transport along predefined paths, involving widely differing surface materials and chemistries.…”
mentioning
confidence: 99%